The Creating Digital Platform Active Learning Supreme Application Using the ADDIE Model to Enhance Learning Management Activities in the 21st century for the Teachers in Thailand - Vicheanpant, Thanyawich (STAI Miftahul Ula Nganjuk, 2024)
This research aims to1) create and to evaluate the effectiveness of digital platform active learning supreme application to promote learning management activities, specifically focusing on the lesson plan the teachers can learn and create lesson plan more effectively and efficiently , as they can learn digital platform active learning supreme application anytime and anywhere and2) to assess the teacher’s satisfaction with using digital platform active learning supreme application The researchers applied the ADDIE Model (Branch,2009)[1] ,a theory of instructional design process that the ADDIE Model starts from the beginning to an end. It contains five phases:1) Analysis 2) Design 3) Development 4) Implementation and 5) Evaluation. The research instrument was the ALS application. ALS application is one of the instructional educations to enhance learning management activities for the teachers. The results of this development research manifest in active learning supreme: ALS application that 1) the quality of the active learning supreme application determined by 5 experts was at the highest level (Mean = 4.72, S.D. =0.40), and2) the instructors were satisfied with active learning supreme: ALS application at a highest level (Mean =4.54, S.D. =0.53). [1] Branch, R. M. (2009). Instructional Design: The ADDIE Approach. New York, NY: Springer. https://doi.org/10.1007/978-0-387-09506-6